2012
DOI: 10.1155/2012/931902
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Transplantation of Allogenic Adult Human Bone Marrow-Derived Mesenchymal Stem Cells into the Subventricular Zone of Parkinson’s Disease: A Pilot Clinical Study

Abstract: The progress of PD and its related disorders cannot be prevented with the medications available. In this study, we recruited 8 PD and 4 PD plus patients between 5 to 15 years after diagnosis. All patients received BM-MSCs bilaterally into the SVZ and were followed up for 12 months. PD patients after therapy reported a mean improvement of 17.92% during “on” and 31.21% during “off” period on the UPDRS scoring system. None of the patients increased their medication during the follow-up period. Subjectively, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 27 publications
2
53
0
Order By: Relevance
“…Moreover, the presence of neural crest derived cells into the adult bone marrow stroma [21], [22] raised new hopes to obtain functional neurons from autologous adult stem cells [8]. Recently, a clinical trial described unilateral transplantation of autologous whole BMSC population into the subventricular zone (SVZ) of PD patients, and reported reserved clinical improvement with no adverse effects, such as tumor formation [29], [30]. Whereas those results were based on clinical observations and Unified Parkinson’s disease Rate Scale scores, the mechanisms underlying the reported improvements are completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of neural crest derived cells into the adult bone marrow stroma [21], [22] raised new hopes to obtain functional neurons from autologous adult stem cells [8]. Recently, a clinical trial described unilateral transplantation of autologous whole BMSC population into the subventricular zone (SVZ) of PD patients, and reported reserved clinical improvement with no adverse effects, such as tumor formation [29], [30]. Whereas those results were based on clinical observations and Unified Parkinson’s disease Rate Scale scores, the mechanisms underlying the reported improvements are completely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Human BMMSCs transfected with the BDNF gene also showed improved functional recovery and reduced infarct size through a reduction in apoptosis [101]. Patients with Parkinson's disease transplanted with BMMSCs in the early stages of the disease (less than 5 years) showed greater improvement than in the later stages (11–15 years) [102]. …”
Section: Bm-derived Mscs (Bmmscs) and Organ Repairmentioning
confidence: 99%
“…Clinical trials have demonstrated that autologous MSC administration is safe using intravenous (IV) administration in ischemic stroke [28] and multiple sclerosis [29] as well as spinal cord transplantation in amyotrophic lateral sclerosis [30] and intracerebral [31,32] and intra-arterial [33] transplantation in PD.…”
Section: Introductionmentioning
confidence: 99%